Dysfunction of natural killer cells promotes immune escape and disease progression in endometriosis - Jiang, Weiyu; Xu, Wen; Chen, Feng (Frontiers in Immunology, 2025)
Endometriosis (EMs) is a chronic inflammatory disorder characterized by dysregulated innate immunity, particularly impaired cytotoxic function of natural killer (NK) cells. As pivotal effectors of the innate immune response, NK cells fail to eliminate ectopic endometrial lesions due to aberrant receptor–ligand interactions, elevated levels of immunosuppressive cytokines (TGF-β, IL-6, and IL-10), and dysfunction of adhesion molecules. This compromised immune surveillance facilitates the survival and implantation of ectopic lesions, contributing to the hallmark symptoms of pain and infertility. Recent immunotherapeutic strategies, including NK cell checkpoint blockade (anti-NKG2A, anti-PD-1), IL-2-based activation, and adoptive NK cell transfer—seek to restore NK cell cytotoxicity and reestablish immune homeostasis. This review summarizes current advances in understanding NK cell dysfunction in EMs, emphasizing its central role in immune evasion and the therapeutic promise of targeting innate immune pathways.